Limitations of Sulforhodamine 101 for Brain Imaging - Hülsmann, Swen; Hagos, Liya; Heuer, Heike; Schnell, Christian (Frontiers in Cellular Neuroscience, 2017)
Since 2004, the red fluorescent dye Sulforhodamine 101 (SR101) has been boosting the functional analysis of astrocytes in a functional environment in an unprecedented way. However, two major limitations have been challenging the usefulness of this tool for cellular imaging: (i) SR101 is not as specific for astrocytes as previously reported; and (ii) discoveries of severe excitatory side effects of SR101 are bearing the risk of unwanted alteration of the system of interest. In this article, we summarize the current knowledge about SR101-labeling protocols and discuss the problems that arise from varying of the staining protocols. Furthermore, we provide a testable hypothesis for the observed hyper-excitability that can be observed when using SR101.